Strategic complexities in the combinatorial clock auction - Stephan Knapek; Achim Wambach (International Telecommunications Society (ITS), 2013)
Recently, the combinatorial clock auction has become more and more common in the auctioning of telecommunication licenses. Although the auction design is complex, the promise is that bidding becomes simple - truthtelling is close to optimal. We show that this claim is too strong. The auction entails several strategic complexities which make bidding non-trivial.
Keywords: 330; combinatorial clock auction